Possible Relationships between Seep Carbonates and Gas Hydrates in the Miocene of the Northern Apennines. (30th June 2011) - Conti, Stefano; Fontana, Daniela
Abstract : In the Miocene of the northern Apennines, a widespread carbonate precipitation was induced by the expulsion of methane-rich fluids. Numerous outcrops of carbonate masses share sedimentological, textural and geochemical features with present-day gas hydrate-associated carbonates. We hypothesize the contribution of paleo-gas hydrate destabilization on the base of the heavy oxygen isotope signature, the presence of distinctive sedimentary features (breccias, pervasive nonsystematic fractures, and soft sediment deformation), the close association between seep carbonates and sedimentary instability, and the huge dimensions of seep carbonates bearing brecciated structures.